Manufacturing and Feasibility Test of Duck Egg Incubator Machine with Automatic System for Small Industrial Scale - Anang, Anang Supriadi Saleh; Subagja, Hariadi; Supriyono (Jurnal Keteknikan Pertanian, 2024)
This research aims to design and test the feasibility of an automatic system duck egg incubator, with 100% local ingredients (TKDN) and affordable for small duck egg hatching industries. Duck egg hatching continues to develop along with advances in technology and the increasing need for duck eggs and cut duck meat. The innovation of the automatic duck egg incubator machine is an effort to help the small duck egg hatching industry to increase production in a more efficient and ergonomic manner. In this research, the creation of an automatic duck egg incubator machine uses stages including problem identification, formulation and refinement of ideas, selection of design concepts, analysis and creation of working drawings, manufacture of tool prototypes, testing and refinement of tool prototypes, then feasibility tests for temperature stability and stability are carried out. humidity, and hatchability tests carried out at the small duck egg hatchery industry UD. Putra Jember, Puger, Jember. The result of this research is an automatic duck egg incubator with a capacity of 5000 eggs, with an LPG heating source. The feasibility test showed stable temperature and humidity fluctuations and produced a hatchability of 82%.